2021
DOI: 10.3390/ijerph182111375
|View full text |Cite
|
Sign up to set email alerts
|

Diet Quality and Incident Non-Communicable Disease in the 1946–1951 Cohort of the Australian Longitudinal Study on Women’s Health

Abstract: Diet quality indices (DQIs) can be useful predictors of diet–disease relationships, including non-communicable disease (NCD) multimorbidity. We aimed to investigate whether overall diet quality (DQ) predicted NCD, multimorbidity, and all-cause mortality. Women from the 1945–51 cohort of the Australia Longitudinal Study on Women’s Health (ALSWH) were included if they: responded to S3 in 2001 and at least one survey between 2004 (S4) and 2016 (S8), and had no NCD history and complete dietary data at S3. DQ was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 102 publications
3
30
0
Order By: Relevance
“…In our study, we did not find any association between DQ and cancer (excluding skin cancer). The previous analysis conducted among the ALSWH cohort showed similar results [ 50 ]. The discrepancies between studies might be partly explained by shorter follow-up durations since cancer cannot be detected within a far shorter period [ 116 ].…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…In our study, we did not find any association between DQ and cancer (excluding skin cancer). The previous analysis conducted among the ALSWH cohort showed similar results [ 50 ]. The discrepancies between studies might be partly explained by shorter follow-up durations since cancer cannot be detected within a far shorter period [ 116 ].…”
Section: Discussionsupporting
confidence: 71%
“…Therefore, in our ALSWH 1973–78 cohort, DQ at S3 was used to examine the association between DQ and incident NCDs during a 15-year follow up (from S4 to S8). The AHEI-2010 was selected based on its relevance to current dietary recommendations [ 71 ], having performed well when critically appraised compared with other DQIs based on a specific dietary pattern [ 72 ], and because it allowed us to make comparisons across generations based on our previous ALSWH 1946–51 cohort analyses [ 50 ]. The detailed scoring of AHEI-2010 is provided in Supplementary Table S2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The association between the mixed diet and weight gain has also been suggested by Tucker et al [ 80 ]. However, it should be generally considered that irrespective of diet type, diet quality and food components (which were absent from investigation in the present study) have been shown to be remarkable predictors of health and weight management [ 19 ], and thus, caution must be warranted when interpreting the findings. Regardless of this fact, plant-based diets have a significant weight-loss effect, which in general terms could be considered positive in those individuals who need to reduce their weight for health purposes [ 78 , 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…Adherence to healthy diets seems to be associated with a better weight-related profile (i.e., lower body mass index (BMI) and waist circumference) [ 17 ]. While certain diet types are associated with a lower incidence of cancer [ 18 ], diet quality is an important predictor of non-communicable diseases and, therefore, could be considered an effective preventive intervention [ 19 ]. In general, healthier diets may lead to higher overall health [ 20 ].…”
Section: Introductionmentioning
confidence: 99%